Risk and protective factors for alcohol, marijuana, and cocaine use among child welfare-involved youth. (December 2018) - Pittenger, Samantha L.; Moore, Kelly E.; Dworkin, Emily R.; Crusto, Cindy A.; Connell, Christian M.
Abstract: Youth involved in child welfare services (CWS) are at elevated risk for substance use. CWS involvement may provide an opportunity for intervention to prevent subsequent use; however, little is known about mitigating substance use risk in this population. Using data from the second National Survey of Child and Adolescent Well-Being (NSCAW II), the present study examined individual, psychological, and contextual risk factors (e.g., prior substance use, depression, posttraumatic stress, maltreatment experiences) and protective factors (e.g., caregiver monitoring, peer relationships) following CWS involvement (Wave 1) in relation to alcohol, marijuana, and cocaine use 36 months later (Wave 3). The nationally-representative sample of CWS-involved youth was restricted to individuals who were aged 11 years or older at Wave 1 and had at least a partial interview at Wave 3 ( N  = 763). Three logistic regression models showed that Wave 1 substance use increased the likelihood of marijuana and cocaine use at Wave 3 [marijuana OR  = 1.41 (1.19–1.68); cocaine OR  = 1.26 (1.07–1.50)] but not binge alcohol use [ OR  = 1.44 (0.95–2.19)]. Other risk and protective factors had limited predictive value for Wave 3 substance use. The present findings suggest that initiating substance use prior to or at the time of CWS involvement is a critical risk factor for later substance use. Substance use screening and referral to treatment is imperative for CWS-involved youth. Highlights: 44% of youth endorse substance use at the time of child welfare involvement Prior illicit substance use predicts future marijuana and cocaine use Youth self-reported behavior problems predict longitudinal cocaine use Protective factors do not influence substance use over time